Discretionary Online Games and Social Skills On Children’s Aggressive Behavior - Qorina Widuri; Yufiarti Yufiarti; Hapidin Hapidin (Universitas Negeri Makassar, 2018)
This study aims to find out the influence of the intensity of playing online games and social skills toward aggressive behavior in 8 years old children using ex-post facto quantitative pathways. This study was conducted in four elementary schools in the city of Bekasi, with 120 total numbers of respondents (N) in 8 years old children who were students in grade two elementary school. This study applies treatment by level 2x2 design. The hypothesis in this study is analyzed by using two-way variant analysis (ANOVA) and Tukey Test. The results of this study shows that 1) there is a significant difference on aggressive behavior in 8 years old children who were intensive and not intensive playing online games; 2) there is a difference on aggressive behavior in 8 years old children who have high social skills and low social skills; and 3) there is a significant influence based on interaction between intensity of playing online games and social skills toward aggressive behavior in 8 years old children in the city of Bekasi.